Understanding Trigeminal Neuralgia: A Comprehensive Review of Symtoms, Diagnosis, and Management - Valentino, Andrea; Mardhiyah, Farah; Maspian Tjili, Tondi; Hadisi, Anthar; Aji Prihartomo, Gatot; Prastya Pardede, Jeremia; Wirdayanto, Ade (Surgical Residency Program Syiah Kuala University, 2024)
Trigeminal neuralgia (tic douloureux) is a rare and debilitating facial pain condition affecting one or more branches of the trigeminal nerve. It is frequently misdiagnosed as a dental issue or temporomandibular disorder due to overlapping symptoms, delaying appropriate treatment. Diagnosis is primarily clinical, often requiring the expertise of a neurologist to distinguish it from other causes of facial pain. Imaging studies such as MRI or CT scans are not diagnostic but play a crucial role in ruling out secondary causes and identifying pathological changes in the affected nerve root. Although not life-threatening, trigeminal neuralgia significantly impacts the quality of life, causing severe, recurrent pain episodes that can be challenging to manage. Timely and accurate diagnosis, along with the implementation of effective therapeutic strategies, is essential to alleviate symptoms and improve patient outcomes. This review highlights the clinical presentation, diagnostic approach, and current treatment modalities for trigeminal neuralgia, emphasizing the importance of a multidisciplinary approach to care.